Determinants of Successful Cooperation in a Face-to-Face Social Dilemma - Silvia Grätz; Donja Darai (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
What makes you a successful cooperator? Using data from the British television game show ``Golden Balls'' we analyze a prisoner's dilemma game and its pre-play. We find that players strategically select their partner for the PD, e.g., they bear in mind whether contestants lied. Players' expectations about the stake size strongly influence the outcome of the PD: The lower the stakes, the more likely players successfully cooperate. Most interestingly, unilateral cooperation is encouraged by mutually promising not to defect and shaking hands on it, but a mere handshake serves as manipulating device and increases successful defection.
Keywords: C72; C93; H41; 330